Novel Extraction Method for Combined Lipid and Metal Speciation From Caenorhabditis elegans With Focus on Iron Redox Status and Lipid Profiling - Blume, Bastian; Witting, Michael; Schmitt-Kopplin, Philippe; Michalke, Bernhard (Frontiers in Chemistry, 2021)
Parkinson´s disease progression is linked to iron redox status homeostasis via reactive oxygen species (ROS) formation and lipids are primary targets of ROS. The determination of iron redox status in vivo is challenging and requires specific extraction methods, which are so far tedious and very time consuming. We demonstrated a novel, faster and less laborious extraction method using the chelator Ethylene glycol l-bis(β-aminoethyl ether)-N,N,N′,N′-tetra acetic acid (EGTA) as stabilizing agent and synthetically quartz beads for homogenization under argon atmosphere. Additionally, we combined the metal extraction with a well-established lipid extraction protocol using methyl-tert-butyl ether (MTBE) to avoid the problems of lipid precipitation in frozen samples and to determine lipid profiles and metal species from the same batch. Non extractable matrix, such as the debris is removed by centrifugation and digested to determine the total metal content of the sample as well. Lipid profiling using RP-LC-MS demonstrated high accordance of the modified extraction method to the reference method and the organic solvent does not affect the iron redox status equilibrium. Furthermore, rigorous testing demonstrated the stability of the iron redox status equilibrium during the extraction process, secured by: complexation, protection atmosphere, fast preparation and immediately deep frozen extracts.